1970
DOI: 10.3126/hren.v9i3.5590
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of mothers regarding breast feeding: a hospital based study

Abstract: Background: Although breastfeeding is a common practice in Nepal, proper breastfeeding is on the decline due to several factors. The impact of knowledge about breastfeeding practice, i.e., duration of breastfeeding, proper techniques, proper time of weaning is poorly understood. Objective: To assess the knowledge and actual practices of mothers regarding breastfeeding. Methods: Cross sectional study was carried out on 200 mothers of under 1 year old children who attending the pediatric Out Patient Department, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
3
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 3 publications
10
71
3
2
Order By: Relevance
“…Chaudhary et al [9] observed that 75% revealed a lack of knowledge about the meaning of exclusive breastfeeding and the importance of night feeding. Ekambaram et al [8] reported that the maternal knowledge was inadequate regarding time to initiate breastfeeding (92%), colostrum feeding (56%), duration of exclusive breastfeeding (38%), and expressed breast milk (51%).…”
Section: Lack Of Knowledge Related To Lactation Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Chaudhary et al [9] observed that 75% revealed a lack of knowledge about the meaning of exclusive breastfeeding and the importance of night feeding. Ekambaram et al [8] reported that the maternal knowledge was inadequate regarding time to initiate breastfeeding (92%), colostrum feeding (56%), duration of exclusive breastfeeding (38%), and expressed breast milk (51%).…”
Section: Lack Of Knowledge Related To Lactation Stimulationmentioning
confidence: 99%
“…[2] [16] According to the literature, antenatal education is an important factor in developing breastfeeding knowledge development and fos-tering breastfeeding skills and confidence for initiating and maintaining breastfeeding until the sixth month, as currently recommended. [2] [4] Nevertheless, Chaudhary et al [9] argued that maternal knowledge about breastfeeding was inadequate, and there was a big gap between actual and desired practices. In turn, others authors claimed that increasing mothers' knowledge was the first step to increase breastfeeding rates and duration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed that 41.5% had started breastfeeding less than one hour. Another study done in Aminu Kano Teaching Hospital, Nigeria to assess the knowledge, attitude and practice of exclusive breastfeeding among multigravid women attending antenatal clinic which showed that 47.2% exclusively breastfeeds for first six months of life 14 .…”
Section: Discussionmentioning
confidence: 99%
“…A crucial role is played by the duration of breast feeding, the time when the baby is weaned and the time of initiation of breast feeding in determining the health of the baby 4 . Chaudhary et al, 5 denoted 'WHO had recommended the immediate initiation of breast feeding after birth preferably within half an hour after delivery. This would enable the baby to get colostrum' .…”
Section: Introductionmentioning
confidence: 99%